Association between educational attainment and blood pressure in older adults: a study of two Finnish generational cohorts born 20 years apart - Ramos Emidio Lääti; Adriana; Somerpalo, Oskari; Teppo, Konsta; Vire, Jenni; Viitanen, Matti; Langen, Ville (Elsevier BV, 2025)
Background: This study compares the association between educational attainment and blood pressure (BP) in two Finnish cohorts of older adults, born 20 years apart.
Methods: All 70-year-old residents of Turku, Finland, were surveyed in 1990 (1920-born TUVA cohort) and in 2010 (1940-born UTUVA cohort). Associations between education and BP were assessed using first ANOVA and post-hoc Tukey tests and then multiple linear regression, adjusted for age, gender, smoking, and body mass index. Analyses included 668 TUVA and 862 UTUVA participants.
Results: In the TUVA cohort (67.7 % women, mean age 70.9), 77.7 % had primary education only, compared to 54.1 % in the UTUVA cohort (59.6 % women, mean age 71.4). ANOVA revealed a significant association between education level and diastolic BP in the UTUVA cohort (p = 0.04). All other ANOVA results were non-significant (p ≥ 0.14). Tertiary education did not have a significant association with BP (p ≥ 0.0544). In regression analyses, each additional year of education in UTUVA correlated with a 0.36 mmHg decrease in systolic BP (p = 0.01) and a 0.32 mmHg decrease in diastolic BP (p < 0.001).
Conclusions: The 1920-born cohort demonstrated no significant differences in BP across education levels, whereas in the cohort born in 1940, higher education was associated with significant but small reductions in BP. These findings suggest that education may be linked to BP, but the absolute differences across education levels are modest. The relationship between education and BP is complex, influenced by lifestyle choices and healthcare access, and requires further exploration.